The Functions, Methods, and Mobility of Mitochondrial Transfer Between Cells - Qin, Yiming; Jiang, Xin; Yang, Qi; Zhao, Jiaqi; Zhou, Qiong; Zhou, Yanhong (Frontiers in Oncology, 2021)
Mitochondria are vital organelles in cells, regulating energy metabolism and apoptosis. Mitochondrial transcellular transfer plays a crucial role during physiological and pathological conditions, such as rescuing recipient cells from bioenergetic deficit and tumorigenesis. Studies have shown several structures that conduct transcellular transfer of mitochondria, including tunneling nanotubes (TNTs), extracellular vesicles (EVs), and Cx43 gap junctions (GJs). The intra- and intercellular transfer of mitochondria is driven by a transport complex. Mitochondrial Rho small GTPase (MIRO) may be the adaptor that connects the transport complex with mitochondria, and myosin XIX is the motor protein of the transport complex, which participates in the transcellular transport of mitochondria through TNTs. In this review, the roles of TNTs, EVs, GJs, and related transport complexes in mitochondrial transcellular transfer are discussed in detail, as well as the formation mechanisms of TNTs and EVs.This review provides the basis for the development of potential clinical therapies targeting the structures of mitochondrial transcellular transfer.